Nanotechnology; its significance in cancer and photodynamic therapy - Mohammad Reza Gaeeni; Morteza Sasani Ghamsari; Marzieh Tohidian; Mohammad Hossein Majles Ara (Nanomedicine Journal, 2015)
In the last decade, developments in nanotechnology have provided a new field in medicine called “Nanomedicine”. Nanomedicine has provided new tools for photodynamic therapy. Quantum dots (QDs) are approximately spherical nanoparticles that have attracted broad attention and have been used in nanomedicine applications. QDs have high molar extinction coefficients and photoluminescence quantum yield, narrow emission spectra, broad absorption, large effective stokes shifts. QDs are more photostable and resistant to metabolic degradation. These photosensitizing properties can be used as photosensitizers for Photodynamic Therapy (PDT). PDT has been recommended for its unique characteristic, such as low side effect and more efficiency. Therefore, nanomedicine leads a promising future for targeted therapy in cancer tumor. Furthermore, QDs have recently been applied in PDT, which will be addressed in this review letter. Also this review letter evaluates key aspects of nano-particulate design and engineering, including the advantage of the nanometer scale size range, biological behavior, and safety profile.